Influence of Two-line Emergent Floodplain Vegetation on a Straight Compound Channel Flow - Jumain, Mazlin; Ibrahim, Zulkiflee; Ismail, Zulhilmi; Ibrahim, Nur Hartini; Makhtar, Md Ridzuan; Nordin, Mohd Rafique (International Journal of Integrated Engineering, 2013)
Abstract: Floods are frequent events occur in Malaysia and cause loss of life, human suffering and widespread damages to buildings, crops and infrastructure. Effort to understanding on this phenomenon is an interesting research. The objectives of this study are to determine the stage-discharge relationship, roughness coefficient and streamwise velocity distribution in a vegetated straight compound channel. The effects of two-line emergent vegetation along the edge of floodplain are studied by using a flume in the Hydraulics Laboratory, Faculty of Civil Engineering, Universiti Teknologi Malaysia (UTM). The results on stage-discharge relationship, Manning’s n and velocity distribution for overbank flows are presented in this paper. From the analysis, it is found that the vegetation influences stage-discharge where retardation of flow takes place. The maximum velocity zone is observed to be in the main channel and less fluid momentum transfer takes place in the presence of vegetation. Vegetated floodplain also influence the increases of channel roughness.